The behavior of implant-supported dentures and abutments using the cemented cylinder technique with different resinous cements - Ivete Aparecida de Mathias Sartori; Geninho Thomé; Caio Hermann; Cláuber Antonio Gomes Borges; Ana Paula Farnezi Bassi (Faculdade São Leopoldo Mandic, 2008)
Objective: Evaluate the behavior of implant-supported dentures and their components, made by cemented cylinder technique, using threetypes of resin cements. Methods: Fifty three patients, of whom 26 were women and 27 men, aged between 25 and 82 years. Results: With partial (54.43%) and total (45.57%) implant-supported dentures, of the Cone Morse, external and internal hexagon types (Neodent®, Curitiba, Brazil), totaling 237 fixations, were analyzed. The resin cements used were Panavia® (21.94%), EnForce® (58.23%) and Rely X® (19.83%) and the components were used in accordance with the Laboratory Immediate Loading - Neodent® sequence. The period of time of denture use ranged between 1 and 5 years. The results reported that 5(2.1%) cylinders were loosened from metal structure (both belonging to Rely X group), 2(0.48%) implants were lost after the first year of use, 16(6.75%) denture retention screws wereloosened and 31(13.08%) abutment screws were unloosened.Conclusion: The reasons for these failures probably are: metal structure internal retention failure, occlusal pattern, cementation technique and loading conditions. The cemented cylinder technique was effective when used in partial and total implant-supported rehabilitations, keeping prosthetic components stable, despite the resin cement utilized. However, further clinical studies must be conducted.